Dobrando a fita: livro-reportagem sobre a memória da peteca em Minas Gerais - Silva, Amanda Franciele (2020)
Shuttlecock is a poorly recognized sport and is seen as recreation. However it has official Confederations, Federations, rules and competitions. This research examines how a relationship between Minas Gerais and the shuttlecock occurs as a sport, that is, how it became an integral part of the culture of Minas Gerais and how the state aided in the recognition and confirmation of the petition during the sport. The study was done through literary journalism, book-report, sports journalism and memory. In the construction of the narrative we used the Greimas operational narrative model and the indicative paradigm of Ginzburg. The final product was the book-reportage-story-essay Folding the tape: memories of miners who do not drop the shuttlecock. The book intersperses past time and presents the sport in Minas Gerais from 1980 to the present day. The narrative is divided into six thematic parts and is constructed from the result of interviews with organizers, teachers, athletes, fans and family members.